Acceptability, simplicity, and relevance of the new human papillomavirus/DNA test among 35-year-old ever-married women in a district of Sri Lanka: focus group discussions - K. C. Perera; K. N. Mapitigama; T. C. Abeysena (BMC, 2022)
Abstract Background Two major drawbacks of the present cervical cancer screening programme in Sri Lanka are, the suboptimal sensitivity of the pap smear and the low coverage. The sensitivity of the HPV/DNA screening test is high. The objective of the study was to explore the acceptability relevance and simplicity of the new HPV/DNA screening implementation among ever-married women in a district of Sri Lanka. Methods Focus group discussions (FGD) (n = 3) in the public health divisions of the Kalutara district were used to collect data during December 2018. The study population comprised of ever-married women 35 years old, who, carried out an HPV/DNA test at a community Well Woman Clinics (WWCs) (n = 89). A list of WWCs was prepared according to an alphabetical order under urban, rural, and estate sector categories and allocated a number. One WWC was selected from each sector randomly for the three FGDs representing the estate, rural, and urban clinics. A convenient sampling technique was used to select participants for each FGD (n = 8). The information collected at each interview was summarized at the end of each interview. The analysis was done with manual content. Results Most of the participants were Sinhalese (n = 17, 70.9%), Buddhist (n = 18, n = 75%), and non-working (n = 18, n = 75%). The community awareness of HPV/DNA screening and field staff performance were highly appreciated by most of the participants. Most were aware of the high sensitivity of the HPV/DNA test, therefore the early detection rate of cervical cancer precursors is high. Most of the participants expressed the HPV/DNA test as a convenient and neutral test. Most were mentioned the necessity of repeated clinic visits for the pap test and colposcopy in HPV/DNA screened positive follow-up but there was marked acceptability (n = 23, 95.8%) for HPV/DNA test. Conclusions Acceptability of the new HPV/DNA screening test was high. Most of the participants perceived the HPV/DNA test to be simple and also relevant. Therefore, the HPV/DNA screening test can be recommended to be incorporated into the National Cervical Cancer Screening Programme as its suitability was well explored in the Sri Lankan setting.